2018
DOI: 10.1016/j.mattod.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Interface affected zone for optimal strength and ductility in heterogeneous laminate

Abstract: Interfaces have been reported to significantly strengthen and toughen metallic materials. However, there has been a long-standing question on whether interface-affected-zone (IAZ) exists, and how it might behave. Here we report in situ high-resolution strain mapping near interfaces in a copper-bronze heterogeneous laminate, which revealed the existence of IAZs. Defined as the zone with strain gradient, the IAZ was found to form by the dislocations emitted from the interface. The IAZ width remained largely cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(113 citation statements)
references
References 42 publications
5
108
0
Order By: Relevance
“…It is not clear how they interact with each other to produce the HDI hardening and HDI stress. Recently, it has been observed that local shear bands are formed across domain boundaries [62]. This might be caused by local interactions between local back stresses and forward stresses.…”
Section: Outstanding Issuesmentioning
confidence: 99%
“…It is not clear how they interact with each other to produce the HDI hardening and HDI stress. Recently, it has been observed that local shear bands are formed across domain boundaries [62]. This might be caused by local interactions between local back stresses and forward stresses.…”
Section: Outstanding Issuesmentioning
confidence: 99%
“…According to the above-mentioned strategies for inducing high back-stress, the heterogeneous lamella structure (HLS) presents a near-ideal heterogeneous structure due to both the high density of domain interfaces and the adjustable volume fractions for soft/hard domains in such microstructure [16,23]. Our recent results have shown that a commercially-pure Ti with HLS, which possesses the spatial distribution of the alternating hard and soft lamellae with their both widths Recent studies on copper/bronze laminates by Huang et al have revealed possible existence of an optimum layer thickness for the best mechanical properties [25,155]. In-situ microstructural examinations during tensile deformation revealed pile up of high-density GNDs at the hetero-interfaces.…”
Section: Heterogeneous Lamella Structuresmentioning
confidence: 71%
“…While too small spacing would cause the overlapping of the distributions of GNDs for neighboring interfaces, resulting in decreasing strain hardening and tensile ductility. Thus, a proper spacing between the hetero-interfaces has been identified to be about 15 µm for generating the best tensile properties for the copper/bronze laminates [25].…”
Section: Heterogeneous Lamella Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, higher flow stress is needed to overcome this field to sustain further plastic deformation. Several studies have reported that high back stress induces strengthening and hardening in heterogeneous-structured materials [8,[33][34][35][36]. To measure the back stress generated during tensile deformation, LUR tests were performed on the GS (PT90, PT180, PT360) and coarse-grained samples.…”
Section: Back Stress Induced Strengthening and Hardeningmentioning
confidence: 99%